Benchmarking business excellence practices: a case-based approach. (26th May 2021) - Mavilavalappil, Unnikrishnan Palakkil; Tikoria, Jyoti; Agariya, Arun Kumar
This paper aims to explore the business excellence practices and the relative importance of success factors by taking a case of an Indian manufacturing organisation for benchmarking purpose. A series of structured, semi-structured, in-depth interviews and company annual reports followed by a questionnaire survey were used to examine current business excellence practices and relative importance of success factors so as to benchmark best in-class practices. Factors namely 'teamwork' and 'culture and core values' are found to be very prominent at the case study of organisation ABC and helped them significantly in enhancing their performance. The rest of the factors are in line with the success factors of prominent global business excellence models. The findings of this study in terms of providing a simple template to assess organisations will be of utmost help to make improvements for moving towards business excellence. The present study reveals that there should be a customisation of the success factors for business excellence based on sector and context specificity.